2020
DOI: 10.1111/eve.13397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of head and tail rope‐assisted recovery of horses after elective and emergency surgery under general anaesthesia

Abstract: The recovery phase is a critical period during equine anaesthesia. In an attempt to reduce the risk of recovery, several recovery systems, including head and tail ropes, have been developed over time. However, the clinical safety and efficacy of these systems have not been compared to a nonassisted group in a larger study. The objective of this comparative, retrospective, nonrandomised single-centre study was to determine whether the risk of developing fatal and nonfatal complications after general anaesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…Anaesthetic-related mortality rates up to seven days after surgery is higher in colics compared with elective procedures (11.7 versus 0.9%) [1]. Nicolaisen et al, (2021) even showed that colic horses are at higher risk to die during recovery when compared to elective and non-nonemergency abdominal procedures [323]. Accordingly, in a further study, recoveries were worse after emergency exploratory laparotomies than those after elective surgeries in dorsal recumbency [371].…”
Section: Other Factorsmentioning
confidence: 93%
See 4 more Smart Citations
“…Anaesthetic-related mortality rates up to seven days after surgery is higher in colics compared with elective procedures (11.7 versus 0.9%) [1]. Nicolaisen et al, (2021) even showed that colic horses are at higher risk to die during recovery when compared to elective and non-nonemergency abdominal procedures [323]. Accordingly, in a further study, recoveries were worse after emergency exploratory laparotomies than those after elective surgeries in dorsal recumbency [371].…”
Section: Other Factorsmentioning
confidence: 93%
“…Head and tail rope assistance is the most frequently used assistance technique [68,69]. Three studies in this review compared the head and tail rope system to unassisted recovery [321][322][323]. Head and tail ropes improved the recovery quality after short elective procedures, which was not shown after long emergency abdominal surgeries [321,322].…”
Section: Recovery Systemsmentioning
confidence: 96%
See 3 more Smart Citations